2020
DOI: 10.32604/phyton.2020.08409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Growth and Cone Traits of Pinus Koraiensis Half-Sib Families in Northeast China

Abstract: Genetic parameters were evaluated for growth and cone characteristics (tree height, diameter at breast height, volume, cone number, thousand seeds weight and single cone seeds weight) on 86 half-sib families of Pinus koraiensis aged 31 years. Analyses of variance revealed significant differences (p < 0.001) in all growth and cone traits among families while no significant differences were detected among blocks and the interaction between blocks and families. The average family values for growth traits were 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…This achievement was superior to that reported on improved Scots pine in northern Finland after clear-cutting [71]. However, the engendered economic value was significantly higher than that reported on sib-families Korean pine [18], which would be due to the difference in planting age and stand density per hectare, which has been mentioned as having an effect on wood yield per hectare in seed orchards [72].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This achievement was superior to that reported on improved Scots pine in northern Finland after clear-cutting [71]. However, the engendered economic value was significantly higher than that reported on sib-families Korean pine [18], which would be due to the difference in planting age and stand density per hectare, which has been mentioned as having an effect on wood yield per hectare in seed orchards [72].…”
Section: Discussioncontrasting
confidence: 65%
“…In fact, estimating economic outcome from improved materials is of great importance to know whether outlay-related investments in tree improvement will be covered [70]. The current price reported for P. koraiensis logs was approximately 145.31 USD per cubic meter in Jilin Province [18]. Considering the average volume of clones (0.418 m 3 ), and the genetic gain of 42.96% in volume for elite clones, the price of a single tree will be increased by 26.093 USD (i.e., 15% of the initial price) and the value of the stand volume per hectare will increase by 5325.10 USD with a plant spacing of 7.0 m × 7.0 m, or a density of 204.081 trees/hectare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic variation parameters evaluated in this work on phenotypic traits seem to be higher, especially in fruit-related traits, with repeatability values up to 90%. A previous study of [65] reported heritability values of less than 0.7 in fruit characteristics while investigating 33 years of Korean pine half-sib families. The variation in environmental conditions in the orchard would have influenced the variation, given significant growth differences from subblocks obtained in several growth characteristics.…”
Section: Clone Variability Based On Phenotypic Characteristicsmentioning
confidence: 95%
“…Seed orchards are established from known materials with the assumption of high performance for industrial, commercial forestry (Hall et al, 2020;Kaviriri et al, 2020). Seed orchards, unlike other commercial plantations, are managed differently in term of wider spacing, pollarding and roguing for robust branching to maximize on seed production (Loewe-Muñoz et al, 2019;Weng et al, 2020;농업생명과학연구, 2019).…”
Section: Introductionmentioning
confidence: 99%